Principles of transaction processing - Bernstein, Philip A. (Morgan Kaufmann series in data management systems., 2009)
Principles of Transaction Processing is a clear, concise guide for anyone involved in developing applications, evaluating products, designing systems, or engineering products. This book provides an understanding of the internals of transaction processing systems, describing how they work and how best to use them. It includes the architecture of Web Application Servers, transactional communications paradigms, and mechanisms for recovering from transaction and system failures. The use of transaction processing systems has changed in the years since publication of the first edition. Electronic commerce has become a major focus for business data processing investments, from banking and stock purchase on the web, to eBay auctions, to corporate database management. New standards, new technology and products, and new languages allow web services and SOA to become the leading style of design for enterprise applications. And with the help of this book and its rich examples, you will be able to produce the state-of-the-art applications discussed within. For more information check out Eric Newcomer's blog: http://ericnewcomer.wordpress.com/2009/05/15/what-we-learned-writing-the-second-edition-of-the-tp-book/ Complete revision of the classic "non mathematical" transaction processing reference for systems professionals. Updated to focus on the needs of transaction processing via the Internet-- the main focus of business data processing investments, via web application servers, SOA, and important new TP standards. Retains the practical, non-mathematical, but thorough conceptual basis of the first edition